Editor's Note = Note du directeur [74, Fall 2014] - Palmer, Bryan D. (Labour / Le Travail, 2014)
The editor announces his retirement and reflects on his longstanding connection with the journal, first as a contributor, then as editor. Expresses appreciation for the work and support of others. Welcomes members of the Canadian Association of Work and Labour Studies to the editorial board as well as incoming editor Sean Cadigan.
Keywords: Editors; PERIODICALS